Effect of Low Dose Oral Contraceptive Pill on Coagulation Status in Women with Normal and Low Body Mass Index (Journal of Bangladesh College of Physicians and Surgeons, 2017)
Background: Oral contraceptive pill (OCP) is widely used by millions of women of various socioeconomic conditions.Use of low dose oestrogen and newer progesterone in OCP now associated with less thromboembolic and cardiovascular risk. The safety aspects of these pills had not been investigated in details in malnourished women of developing countries. In the present study the effects of the pillson coagulation status have been studied.Objective: To explore the effect of the most widely used low dose OCP (Shukhi) on coagulation status of Bangladeshi women with normal and low BMI(Body Mass Index). Materials and Methods: The study population group (n=29) comprised of women with normal BMI and the underweight group (n=11,BMI